Recent Advances in Epidural Analgesia. (9th October 2011) - Bauer, Maria; George, John E.; Seif, John; Farag, Ehab
Abstract : Neuraxial anesthesia is a term that denotes all forms of central blocks, involving the spinal, epidural, and caudal spaces. Epidural anesthesia is a versatile technique widely used in anesthetic practice. Its potential to decrease postoperative morbidity and mortality has been demonstrated by numerous studies. To maximize its perioperative benefits while minimizing potential adverse outcomes, the knowledge of factors affecting successful block placement is essential. This paper will provide an overview of the pertinent anatomical, pharmacological, immunological, and technical aspects of epidural anesthesia in both adult and pediatric populations and will discuss the recent advances, the related rare but potentially devastating complications, and the current recommendations for the use of anticoagulants in the setting of neuraxial block placement.